'I AM THE MOTHER AND THE FATHER' - WOMEN IN CONSTRUCTION IN CUBA AND THE UK. (1st April 2010) - Unknown
Abstract : Construction ranks as one of the most gender segregated sectors worldwide, whilst gender diversity is now considered a success factor in economic growth and social welfare. The aim of this article is to evaluate the progress made by women in Cuba in making inroads into this male-dominated work sector, building on theoretical perspectives in relation to working in construction and women's gender roles which have been developed in both Cuba and the UK. Drawing on interviews with Cuban women in construction, it seeks to find answers to the questions of why women should choose to go to work in this environment despite the barriers, whether there are good reasons for society needing them to do this kind of work and what conditions need to be put in place in order to make this possible. These questions are evaluated in relation to the triple burden of paid work, combating exclusion, and unpaid work in the home; and conclusions are drawn for future study.